Baastrup's disease in the pediatric spine - Singh, Suryapratap (Asian Journal of Neurosurgery, 2016)
Baastrup's disease is an uncommon entity in the elderly spine and it is very rare in the pediatric age group. There are only few case reports in the literature containing Baastrup's disease in pediatric spine. Baastrup's disease is also known as kissing spine because the posterior spinous processes touch or “kiss” one another, characterized by enlarged posterior spinous projections with normal neuroforamina and normal spinal disk height. There are various pathological and etiological hypotheses behind Baastrup's disease. Backache is one of the most common causes of morbidity in these patients and but sometimes patient can be asymptomatic with or without swelling on the back. Here, we present a case of 10-year-old female child with silent swelling on low back region diagnose as Baastrup's disease.
Keywords: Baastrup's disease; kissing spine; pediatric